Assessment the Vulnerability of Infrastructures in Ardabil City in terms of passive defense - Mohammad Hasan Yazdani; saidain (تحقیقات کاربردی علوم جغرافیایی)
At the moment with regard to geopolitical and geostrategic situation of Iran, the existence of countless underground resources and the formation of ideological state, unfortunately, in urban areas of the country, especially in Ardabil ,because of its proximity to the border of northern and northwestern borders with knowledge of this particular situation, economic and infrastructural projects, Infrastructures and installations have been made without observing and interference of considerations and defense and security arrangements and have become a bare and significant available target for enemy and invading countries. This research aimed to study the vulnerability of Infrastructures Ardabil in terms of passive defense and application - development approach in a descriptive and analytical way using 18 effective indicators in form of 5 components of "Lifeline", "crisis management Centers", "military and police centers", "Urban equipment" and "support centers" in three priorities of strategic, psychological and support destruction. Information gathered in the Super Decision software (network analysis) are weighted, then mapped in GIS environment. The results of the studies show that there are six major hazardous zones under crisis conditions and are prone to injury in the Ardabil that the most important of them are the northeast output of Ardabil (Jahad field leading to Astara gate), the southwest of Ardabil (Sarein station leading to the Basij field toward the Sham Asbi village) and finally the north and northwestern parts of Ardabil (Vahdat square), with the sum of (17% of the total land area of the city) have included the highest vulnerability, due to the poor conditions of the physical characteristics and focus on management, corporate, military and state entities in this regions of the Ardabil city.